Republic of Slovenia : 2016 Article IV Consultation-Press Release and Staff Report for the Republic of Slovenia. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses recent economic developments, outlook, and risks in Slovenia. Although strong demand in trading partners and large European Union structural fund transfers buoyed growth in 2014-15, the outlook is less reassuring. The short-term outlook is broadly balanced, while medium-term prospects are subject to downside risks. Significant structural reforms are needed to realize Slovenia's growth potential, but political tensions and coalition discussions may affect their pace and ambition. Slovenia needs to avoid complacency; with more ambitious reforms, growth can be faster and more sustainable. Concrete measures need to be taken to address binding constraints on growth and reduce financial and fiscal vulnerabilities.